Turning Away From Averted Gazes: The Effect of Social Exclusion on Gaze Cueing - Capellini, Roberta; Riva, Paolo; Ricciardelli, Paola; Sacchi, Simona (Frontiers in Psychology, 2019)
Past studies showed increased sensitivity to other people’s gaze after social exclusion. In the present research, across two studies, we tested whether social exclusion could affect the basic cognitive phenomenon of gaze cueing effect, namely, the tendency to redirect visual attention to the same location that other people are looking at. To this purpose, participants were socially excluded or included using the Cyberball manipulation. In Study 1, after the manipulation, participants performed a gaze cueing task in which an individual’s gaze, oriented rightward or leftward, preceded a peripheral target stimulus requiring a simple categorization response. The gaze direction could be congruent or incongruent with the location of the target. Results revealed a reduced gaze-cueing effect for socially excluded than for socially included participants. In Study 2, where human gazes were replaced by arrow cues, such an interaction between social exclusion and trial congruency disappeared, indicating a specific effect of social stimuli. We interpreted these findings with the notion that excluded participants can perceive an averted gaze as a further sign of social exclusion, thus showing a reduced gaze-cueing effect.